PERSAMAAN REGRESI LINIER BERGANDA UNTUK MEMPREDIKSI EFISIENSI BOILER - Eko Sarwono; Martin Choirul Fatah; Brunner, I Made Indradjaja Marcus Brunner (Jurnal Rekayasa Mesin, 2024)
Boiler efficiency calculation is crucial to determine the reliability of boiler performance. Generally, boiler efficiency is calculated by the heat loss method, which considers losses in the combustion process. The calculation consumes more time due to detailed procedure and analysis. This research aims to develop a multiple linear regression equation in predicting boiler efficiency based on performance test data from PLTU X unit 1. The equation was then validated with a classical assumption test, i.e. normality, linearity, multicollinearity, heteroscedasticity, autocorrelation, and hypothesis test. In addition, the equation was used to calculate the boiler efficiency at PLTU ABC (unit 1 & 2) and PLTU XYZ (unit 1). The results show that there is approximately 0.49% boiler efficiency discrepancy among equation and heat loss method calculations.